The Effects of Different Bracket Types on Orthodontic Treatment Evaluated with the Objective Grading System - Suli Andryani; Nazruddin Nazruddin; Siti Bahirrah (Faculty of Dentistry, Trisakti University, 2019)
Background: Standard edgewise and preadjusted Roth are two bracket types widely used for orthodontic treatment. Whether one of these bracket types offers better treatment results than the other requires further evaluation. The Objective Grading System created by the American Board of Orthodontics (ABO) is one of the most reliable indices used to evaluate treatment outcomes. Objectives: To determine the effects of using two different bracket types on treatment outcomes by using the Objective Grading System. Methods: The sample for this study consisted of 64 randomly selected post-treatment dental casts and panoramic radiographs. Of these samples, 32 were treated with a standard edgewise bracket, and the others were treated with a preadjusted Roth bracket. Patient samples were included if they had non-extraction Class I malocclusion (minor crowding < 4 mm for both bracket types, ANB = 2º ± 2º), no history of dental trauma, complete teeth (except third molars), and no growth or development disturbances. All samples were evaluated using eight parameters of the Objective Grading System and statistically analyzed using Mann–Whitney and chi-squared tests. The score range for each tooth in each parameter was 0 – 2. Results: The total score was 19.00 ± 12.00 for the standard edgewise bracket and 15.00 ± 7.00 for the preadjusted Roth bracket, with no statistically significant differences between the two bracket types (p = 0.149). There were also no statistically significant differences in the scores of the eight parameters of the Objective Grading System between these brackets (p > 0.05). The highest score was found for the buccolingual inclination parameter, and the lowest score was for interproximal contacts. Conclusion: According to the Objective Grading System, there are no statistically significant differences between the orthodontic treatment outcomes obtained using a standard edgewise or a preadjusted Roth bracket.